Moderating effects of perceived supports for creativity on the relationship between individual factors and creativity among Malaysian research officers - Katimin, Muhammad Farihin (2015)
The subject of employee creativity has been widely discussed in the field of human resource development. A variety of factors that promote creativity among employees have been presented. This study addresses the issue of the development of employee creativity with special attention to creative works among research officers in Malaysia. A creativity model of employee characteristics was tested. This model encompassing the individual factors (openness to experience, creative self-efficacy, intrinsic motivation and positive affect), dimensions of creativity (fluency, flexibility, originality and elaboration) and perceived supports for creativity. A survey was conducted on 400 research officers working at one of Malaysia’s largest public research institute, with a return of 286 responses. A check on missing data, outliers and normality analysis was performed. Hierarchical regression analysis confirmed that only a few of the hypotheses developed earlier were supported. Only three out of 16 direct effects of individual factors on creativity were found significant i.e., openness on fluency, openness on elaboration and creative self-efficacy on originality. Moreover, only three out of 48 moderating effects of perceived supports for creativity were found significant i.e., the moderating effects of organisational support in a relationship between creative self-efficacy and fluency, the moderating effects of organisational support in a relationship between intrinsic motivation and fluency and the moderating effects of supervisor support in a relationship between intrinsic motivation and fluency. This suggests that there are several factors based on the Malaysian culture that influence the results which are different from the expected results from the literature. It is also suggested that several parts of this research are to be improved such as the use of structural equation modelling and the use of a better creativity instrument. In conclusion, it is confirmed that in the Malaysian context, level of creativity is high among research officers, however only certain individual factors found to influence creativity. Meanwhile only some moderating effects are found to intensify the relationship between individual factors and creativity